The fruit of her hands: Jewish and Christian women's work in medieval Catalan cities - Ifft Decker, Sarah (Iberian encounter and exchange, 2022)
Marriage and inheritance in Catalan Christian legal culture -- Gender, acculturation, and resistance in Catalan Jewish family law -- Christian women in notarial culture -- Jews, notaries, and the Christian city -- Working women in medieval Catalan cities -- Christian and Jewish women in the interreligious real estate market -- Credit, change, and crisis in Catalan Jewish communities.